Using Neural Circuit Interrogation in Rodents to Unravel Human Speech Decoding - Neophytou, Demetrios; Oviedo, Hysell V. (Frontiers in Neural Circuits, 2020)
The circuits responsible for social communication are some of the most important and least understood in the brain. Human studies have made great progress in advancing our understanding of the global computations required for processing speech, and animal models offer the opportunity to discover evolutionarily conserved mechanisms for decoding these signals. In this review we describe some of the most well-established speech decoding computations from human studies and describe animal studies designed to reveal potential circuit mechanisms underlying these processes. Human and animal brains must perform the challenging tasks of rapidly recognizing, categorizing, and assigning communicative importance to sounds in a noisy environment. The instructions to these functions are found in the precise connections neurons make with one another. Therefore, identifying circuit-motifs in the auditory cortices and linking them to communicative functions is pivotal. We review recent advances in human recordings that have revealed the most basic unit of speech encoded by neurons, and relate these findings to circuit-mapping studies in rodents that have shown potential connectivity schemes to achieve this. Finally, we discuss other putative important processing features in humans like lateralization, sensitivity to fine temporal features, and hierarchical processing. The goal is for animal studies to investigate neurophysiological and anatomical pathways responsible for establishing accessible behavioral phenotypes that are shared between humans and animals. This can be accomplished by establishing cell types, connectivity patterns, genetic pathways and critical periods that are relevant in the development and function of social communication.